Neuropeptide S Displays as a Key Neuromodulator in Olfactory Spatial Memory. (3rd February 2020) - Wang, Can; Xin, Le; Cai, Chen-Chen; Cong, Chao-Yu; Xie, Jun-Fan; Kong, Xiang-Pan; Dong, Chao-Yu; Li, Jing; Cui, Guang-Fu; Chen, Hai-Lin; Ren, Yan-Li; Shao, Yu-Feng; et al.
Abstract: Neuropeptide S (NPS) is an endogenous peptide recently recognized to be presented in the brainstem and believed to play an important role in maintaining memory. The deletion of NPS or NPS receptor (NPSR) in mice shows a deficit in memory formation. Our recent studies have demonstrated that central administration of NPS facilitates olfactory function and ameliorates olfactory spatial memory impairment induced by muscarinic cholinergic receptor antagonist and N -methyl-D -aspartate receptor antagonist. However, it remains to be determined if endogenous NPS is an indispensable neuromodulator in the control of the olfactory spatial memory. In this study, we examined the effects of NPSR peptidergic antagonist [D-Val 5 ]NPS (10 and 20 nmol, intracerebroventricular) and nonpeptidergic antagonist SHA 68 (10 and 50 mg/kg, intraperitoneal) on the olfactory spatial memory using computer-assisted 4-hole-board olfactory spatial memory test in mice. Furthermore, immunofluorescence was employed to identify the distributions of c-Fos and NPSR immunoreactive (-ir) neurons in olfactory system and hippocampal formation known to closely relate to the olfactory spatial memory. [D-Val 5 ]NPS dosing at 20 nmol and SHA 68 dosing at 50 mg/kg significantly decreased the number of visits to the 2 odorants interchanged spatially, switched odorants, in recall trial, and simultaneously reduced the percentage of Fos-ir in NPSR-ir neurons, which were densely distributed in the anterior olfactory nucleus, piriform cortex, subiculum, presubiculum, and parasubiculum. These findings suggest that endogenous NPS is a key neuromodulator in olfactory spatial memory.